Electronic mail management: A corporate memory towards organizational performance - Hussin, Nurussobah; Mohamed, Haslinda; Tarmuchi, Nor Rashimahwati (2008)
This study evaluates government practices in electronic mail (email) management to identify perception on the email management’s contribution as a corporate memory towards organizational performance.The study uses questionnaires as the instrument and a sample of 250 respondents from various government officers in Putrajaya, Malaysia participated in this survey.The study aims to investigate the practices at the government agencies in applying records management principles to email, such as separating email information from email records in the circulation and dissemination process, storing emails, and applying retention and disposal management.The result reveals that the respondents perceive that the documents send through emails contribute to the better performance of their departments.